Appraisal of urban trees using twelve valuation formulas and two appraiser groups (2017)
Monetary valuation using urban tree appraisals can be performed with formulas, a common practice in many countries. This study compares twelve parametric type formulas: Amenity Valuation of Tree and Woodlands (Helliwell), Standard Tree Evaluation Method (STEM), French Method, Italian Method, Tedesco, Norma Granada, Trunk Replacement Formula (CTLA), Burnley Method, Danish Method, Swiss Method, and two Chilean formulas used in Municipalities of Concepción, La Pintana, and Maipú (COPIMA Method), and Peñalolén Method. Formulas were then applied to 30 trees located in Santiago, Talca and Concepción, Chile. Researchers used eight appraisers divided into two groups, according to senior-level and junior-level experience. Statistical differences were determined using the Kruskal-Wallis test of non-parametric variance, while Fisher's least significant difference test was used to identify homogeneous groups. The results show a wide dispersion of values that were high for 'emblematic' trees and low for young or low-vigor trees. Formula, type of appraisers, and inter-appraiser differences formed nine, two, and three groups, respectively. The lowest-appraised trees were obtained using the Danish and French Method, while the highest values were obtained with the Burnley, Helliwell, and STEM formulas. Although there were differences in tree value according to the type of appraiser, when comparing difference among appraisers, researchers found these were not due to experience level. Given the wide range of values found, the study authors cannot recommend any specific formula(s) for assessing urban trees, as results will depend on the variables of interest used in the formulas and their intended application and use. © 2017 International Society of Arboriculture.